KONSEPSI ARAH BAGI ORANG JAWA (Tinjauan Antropologi Linguistik) - Dwi Cahyono Aji (Sunan Kalijaga State Islamic University Yogyakarta, 2010)
Language reflects human conceptualization as how the Javanese conceptualize their ideas and thought in their utterances. The Javanese utterances usually use the lexicon of direction in their daily activities, such as in telling places, jobs, phatic communication, etc. The culture-specific values of the Javanese people are often revealed through languagespecific expressions, especially about the giving direction. The method of analyzing data uses referential identity method with the basic technique of dividing-key-factors and competence-in-dividing. The result of the research shows: 1. All aspects of the Javanese life involves the sense of directions such as North, South, West, East, and Central. 2. The Javanese use lexicons of the sense of direction in their daily activities such as in telling places, jobs, and phatic communication. By knowing this concept of direction, the Javanese’s perspective of the world can be understood.